SOCIOECONOMIC INEQUALITIES IN THE RURAL AREA REGIONAL ANALYSIS - Florian, Violeta (Economics of Agriculture, 2012)
The complexity and extent of inequality, the existing interdependencies between different aspects of individuals life and their impact on human development, in general, is one of the most controversial aspects of economic and social discourse, globally and locally in recent years. In this context, the present study aimed at assessing the socio-economic inequalities in the Bucharest – Ilfov Region, inequalities that take many facets. This objective was achieved using a set of dimensions and indicators describing the condition and extent of rural inequality.